Strengthening the Strategic Thinking Competency of Junior High School Teachers Through Education for Sustainable Development-Based Scenario Training - Suhendar Suhendar; Syane Triwulandari; Asriyanik Asriyanik (Samakta: Jurnal Pengabdian Kepada Masyarakat, 2026)
Education faces a major challenge in preparing a generation capable of responding to uncertainties caused by climate change and the sustainability crisis. The Education for Sustainable Development framework emphasizes strategic thinking competence as the ability to design adaptive actions based on systemic analysis and future projections. However, learning practices in schools still tend to present climate change in an informative manner without training students’ anticipatory capacity. This community service program employed a Participatory Action Research (PAR) approach to strengthen junior high school teachers’ strategic thinking competence through ESD-based scenario training. Seventeen teachers in West Java participated in an online training program consisting of planning, action, observation, and reflection cycles. The activities included strengthening ESD concepts, scenario development techniques, and contextual climate change module design. Evaluation was conducted through pretest–posttest comparison and rubric-based module assessment. The results showed an increase in the average score from 67 to 84. The teaching modules produced demonstrated teachers’ ability to identify driving forces, formulate key uncertainties, and design multiple logical and contextual future scenarios. The program effectively enhanced teachers’ pedagogical capacity and contributed to the transformation of future-oriented learning practices.